Kemampuan Literasi Matematika Siswa dalam Menyelesaikan Soal PISA Ditinjau dari Adversity Quotient - Nanda Triandanu Nilasari; Dewi Anggreini (Universitas Hamzanwadi, 2019)
The purpose of this study was to describe students' mathematical literacy in solving PISA problems with Adversity Quotient (AQ) type of Climber, Camper, and Quitter. This type of research is a qualitative descriptive study with a form of case study research. The subjects of this study were students of class IX 1 of SMP Negeri 3 Tulungagung who had AQ types of climber, camper, and quitter. Data collection was carried out by giving Stoltz's modified ARP questionnaire to determine research subjects, PISA test questions, and interview. Data were analyzed using a Miles and Huberman’s model, which include: data reduction, data presentation, and conclusion/ verification. The results of this study indicate that mathematical literacy ability of Climber‘s student is at 5th level, which was shown to be able to solve PISA problems of 1st level to 5th level and not right in solving of 6th level. Mathematical literacy ability of Camper’s student is at 4th level, which was shown to be able to solve PISA problems of 1st level to 4th level and not right in solving of 5th level and 6th level. Mathematical literacy ability of Quitter’s student is at 4th level, which was shown to be able to solve PISA problems of 1st level to 4th level, besides that it was not right in solving of 5th level and not able to solving of 6th level.